The Extent of Practice of Academic Freedom among Faculty Members and its Relation to the Level of Organizational Health at Jordanian Universities - Al-Omari, Aieman Ahmad; Al-Ghwairin, Yousef F. (Dirasat: Educational Sciences, 2020)
This study aims to identify the extent of practice of academic freedom among faculty members and its relation to organizational health at Jordanian universities. It also aims to find out whether there are significant differences in the extent of practice of academic freedom and the level of organizational health from the viewpoint of faculty according to gender, rank, years of experience, college and university. The study sample was (272) faculty members, selected in a stratified cluster in a random method. The study found that the extent of practice of academic freedom among faculty members and the level of organizational health were medium., and that there are no differences between the extent of practice of academic freedom and the level of organizational health among faculty members due to gender, academic rank, years of experience, or college. There found statistical differences in the level of organizational health attributed to the variable in the 7th field scale (i.e., creativity), and for private universities. In addition, we found a positive correlation between the extent of practice of academic freedom and the level of organizational health from the viewpoint of faculty members. The study recommends raising awareness of the concept of academic freedom and organizational health through seminars, conferences and various media and social networking staff.